THE MEDIATION MECHANISM OF ETHICAL CLIMATE IN THE RELATIONSHIP OF ETHICAL LEADERSHIP AND INTERNAL WHISTLEBLOWING INTENTION - ShiYong, Zheng; Mirza, Salman; Ali, Rizwan; Mehar, Shaza; Hussain, Muzamal; Basharat, Saher (The journal of contemporary issues in business and government, 2022)
A Firm’s unethical practices may deteriorate its performance, slow down its growth, and lastly affect the goodwill of the firm. Florseplay and malpractices significantly influence the organizations, humans, and even societies. The Ann’s employees can perfonn a crucial role in the finding of malpractices in the film and they can report it to the upper authorities through proper reporting channels. But, due to the fear of retribution, they remain silent. In this regard, an ethical-leader can play a crucial function to motivate subordinates towards internal whistleblowing by providing them a moral atmosphere, so, they can report horse-play to the appropriate authorities without any fear. This research study investigates the effect of ethicalleadership on the internal whistle-blowing intentions and the mediation result of an ethicalclimate between ethical-leadership and internal whistle-blowing intentions. Researchers collected data through a survey from the education sector. This study demonstrates the positive result of ethical-leadership on internal whistle-blowing intentions and ethical climate is positively mediated between the ethical-leadership and the internal whistle-blowing intentions. This research has also discussed Theoretical and practical implications.